Industrial structure and regional employment dynamics - Wolfgang Dauth (W. Bertelsmann Verlag (wbv), 2012)
Is there a relationship between a region's industrial structure and employment growth? Wolfgang Dauth pursues this question in three self-contained studies. These studies each examine a different aspect of this topic and form the three main chapters of this book. Chapter 2 ('Agglomeration and regional employment dynamics') documents the significance of positive agglomeration externalities for regional labor markets. Employment growth is more sustainable in industrial agglomerations than in other local industries. In Chapter 3 ('The mysteries of trade'), the sources of agglomeration externalities are explained through linkages between different, but related, industries. The main conclusion is that labor market pooling plays a key role. In Chapter 4 ('The rise of the East and the Far East'), Dauth examines how regional labor markets with differing industrial structures react to increasing exposure to international trade. He shows that Germany as a whole has experienced substantial gains in employment due to the economic rise of China and Eastern Europe. – – Gibt es einen Zusammenhang zwischen der regionalen Branchenstruktur und der Beschäftigungsentwicklung? Wolfgang Dauth ist dieser Frage in drei eigenständigen Studien auf den Grund gegangen. Sie beleuchten jeweils unterschiedliche thematische Teilaspekte und werden in den drei zentralen Kapiteln dieses Bandes behandelt: Kapitel 2 ("Agglomeration and regional employment dynamics") belegt die Existenz von Agglomerationsvorteilen für den regionalen Arbeitsmarkt: In agglomerierten lokalen Branchen ist das Beschäftigungswachstum nachhaltiger als in nicht-agglomerierten. In Kapitel 3 ("The mysteries of trade") wird analysiert, inwiefern die Wechselwirkungen zwischen unterschiedlichen, aber verwandten Branchen die Existenz von Agglomerationsvorteilen erklären. Gemeinsame Arbeitsmärkte, so das zentrale Ergebnis, spielen dabei eine Schlüsselrolle. In Kapitel 4 ("The rise of the East and the Far East") untersucht Dauth, wie sich der internationale Handel auf Regionen mit unterschiedlicher Branchenstruktur auswirkt. Er weist nach, dass Deutschland durch den wirtschaftlichen Aufstieg Chinas und Osteuropas unterm Strich massive Beschäftigungsgewinne verzeichnen konnte.
Keywords: 330; Agglomerationseffekt; Regionaler Arbeitsmarkt; Beschäftigungseffekt; Interindustrielle Verflechtung; Wirtschaftsstruktur; Export; Deutschland; Import; China; Osteuropa; Agglomerationseffekt; Regionaler Arbeitsmarkt; Beschäftigungseffekt; Interindustrielle Verflechtung; Wirtschaftsstruktur; Export; Deutschland; Import; China; Osteuropa